2011
DOI: 10.1002/jmor.10995
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cranial form and function in association with diet in natricine snakes

Abstract: The skull of squamates has many functions, with food acquisition and ingestion being paramount. Snakes vary interspecifically in the frequency, size, and types of prey that are consumed. Natural selection should favor phenotypes that minimize the costs of energy acquisition; therefore, trophic morphology should reflect a snake's primary prey type to enhance some aspect of feeding performance. I measured 19 cranial variables for six natricine species that vary in the frequency with which they consume frogs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 56 publications
3
50
0
1
Order By: Relevance
“…The cause of this pattern is uncertain but may be related to a dietary shift from fish to frog prey. For instance, a comparison of cranial bones among natricines indicated that anurophagous species tend to have wider cranial components than their piscivorous relatives (Hampton, 2011b). Mori and Vincent also found that a frog specialist snake species had a wider head than a syntopic generalist species (Mori and Vincent, 2008).…”
Section: Discussion Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of this pattern is uncertain but may be related to a dietary shift from fish to frog prey. For instance, a comparison of cranial bones among natricines indicated that anurophagous species tend to have wider cranial components than their piscivorous relatives (Hampton, 2011b). Mori and Vincent also found that a frog specialist snake species had a wider head than a syntopic generalist species (Mori and Vincent, 2008).…”
Section: Discussion Morphologymentioning
confidence: 99%
“…For example, increased piscivory in natricines is associated with an increase in quadrate length, which may help maneuver the head around oblong shapes and erect spines (Vincent et al, 2009). In contrast, anurophagous snakes tend to have comparatively wider heads than generalist or piscivorous snakes (Mori and Vincent, 2008;Hampton, 2011b). Prey size can also affect head size and skull dimensions (Aubret et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The effects include adaptation of the jaw apparatus (e.g. Rodriguez-Robles et al, 1999;Ferry-Graham et al, 2002;Van Cakenberghe et al, 2002;Metzger and Herrel, 2005;Santana et al, 2010;Hampton, 2011;Perry et al, 2011), teeth (e.g. Hotton, 1955;Herrel et al, 1997;Herrel et al, 2004;Santana et al, 2011;Kupczik and Stynder, 2012), hyolingual apparatus (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hampton (2011) demonstrated that wider heads may be important for frog capture and Brecko et al (2011) indicated that snakes that ate frogs had wider heads. Conversely and controlling for snake size, banded watersnakes (N. fasciata) that ate frogs had smaller heads than fish-eating individuals (Vincent et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…I individually regressed each of the 6 head metrics against SVL, which yielded size-adjusted head metric residuals to eliminate the effect of larger snakes having larger heads in analyses (Vincent et al 2004a, Hibbits and Fitzgerald 2005, Vincent et al 2006a, Brecko et al 2011, Hampton 2011. To investigate the differences in head morphology among watersnake species and sex, a principal component analysis (PCA) was performed on the resulting head metric residuals.…”
Section: Methodsmentioning
confidence: 99%